Teenagers’ Perception of Da’wah in Constructing Good Morality - Nasor, Muhammad; Rifai, Rendra Nasrul; Utama, Esen Pramudya; Sari, Nina Ayu Puspita (Jurnal Ilmiah Peuradeun, 2022)
This study investigated how the caretaker of the Al-Mukhlisin mosque, Korpri Raya, Sukarame, Lampung Province, conducts da'wah activities to equip teenagers with good morality. The research method employed was a descriptive-qualitative method to describe the teenagers' perceptions of the da’wah activities. The data were obtained through two sources, namely primary data sources and secondary data sources. The primary data sources were the mosque management and the teenagers who participated in the AlMukhlisin mosque da’wah program. The samples were determined through purposive and snowball sampling techniques. The secondary data sources were obtained by collecting documents, records, regulations, supporting books, and literature. This study revealed that teenagers believed that da’wah activities are an obligation for every ummah and serve as places of education. There is a big contribution that the da’wah activities are the agent of change that is trying to change the atmosphere from bad conditions to better conditions. Islamic da’wah seeks to develop the teenagers' ability to live in plurality, to respect other religious communities, and to strengthen the silaturahmi (brotherly bonds).